2017
DOI: 10.18632/oncotarget.18293
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation/hydroxymethylation in melanoma

Abstract: Melanoma is a malignant tumor of melanocytes and is considered to be the most aggressive cancer among all skin diseases. The pathogenesis of melanoma has not been well documented, which may restrict the research and development of biomarkers and therapies. To date, several genetic and epigenetic factors have been identified as contributing to the development and progression of melanoma. Besides the findings on genetic susceptibilities, the recent progress in epigenetic studies has revealed that loss of the DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 113 publications
2
36
0
Order By: Relevance
“…There have been studies suggesting the involvement of DNA methylation with the melanocyte lineage or pigmentation disorders, and most of them examined changes in melanoma . In this study, we revealed the significance of DNA methylation in the pigmentation in SLs, which we believe is a great step for further understanding of how UV radiation affects our skin.…”
Section: Discussionmentioning
confidence: 56%
“…There have been studies suggesting the involvement of DNA methylation with the melanocyte lineage or pigmentation disorders, and most of them examined changes in melanoma . In this study, we revealed the significance of DNA methylation in the pigmentation in SLs, which we believe is a great step for further understanding of how UV radiation affects our skin.…”
Section: Discussionmentioning
confidence: 56%
“…Many critical genes involved in the progression of melanoma from melanocytes have been documented to acquire changes in their methylation. The expression of cyclin‐dependent kinase inhibitor 2A ( CDHN2A ) has been shown to be inactivated by promoter hypermethylation in cutaneous melanoma, which encodes p16 cell cycle inhibitor protein belonging to INK4a/ARE family . The p16 protein inhibits the cell cycle progression through inactivation of CDK‐cyclin complexes.…”
Section: Dna Methylation In Melanomamentioning
confidence: 99%
“…Methylation‐dependent DNA binding proteins (MBDs) spontaneously bind to the hypermethylated sites of the promoter regions, which further assist in silencing of genes by recruiting transcriptional repressor complexes . In addition to the MBDs, methylated regions also bind with histone deacetylases (HDACs) and other chromatin remodeling proteins . HDACs remove the acetyl groups from histone tails which lead to chromatin condensation .…”
Section: Dna Methylation In Melanomamentioning
confidence: 99%
See 2 more Smart Citations